2020
DOI: 10.1111/jonm.12905
|View full text |Cite
|
Sign up to set email alerts
|

Nursing resource team capacity planning using forecasting and optimization methods: A case study

Abstract: Aim To estimate the cost‐minimizing size and skill mix of a nursing resource team (NRT). Background Nurse absences can be filled by an NRT at lower hourly cost than staffing agencies or nurses working overtime, but an NRT must be appropriately sized to minimize total cost. Methods Using all registered nurse (RN) absences at an academic teaching hospital from 1 October 2014 to 31 March 2018, we developed a generalized additive model (GAM) to forecast the weekly frequency of each of ten types of absence over 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Articles of this type show, via feedback from those questionnaires that a multi-disciplinary approach is needed to comprehensively address the hospital capacity optimisation problem. Kaw et al [63] demonstrated a nursing staff cost reduction of 7% by analysing past nurse absences and developing a mixed-integer program to minimise costs subject to the size and skill mix of a nursing resource team, overtime costs and casual staff costs.…”
Section: Human Resourcesmentioning
confidence: 99%
“…Articles of this type show, via feedback from those questionnaires that a multi-disciplinary approach is needed to comprehensively address the hospital capacity optimisation problem. Kaw et al [63] demonstrated a nursing staff cost reduction of 7% by analysing past nurse absences and developing a mixed-integer program to minimise costs subject to the size and skill mix of a nursing resource team, overtime costs and casual staff costs.…”
Section: Human Resourcesmentioning
confidence: 99%
“…In reviewing the literature, a nurse resource team has been defined as a float pool, flex pool, or nursing resource team aimed at addressing staffing issues. 10,11 There is a scarcity of reports on a critical care clinical resource nurse dedicated to coverage outside the ICU. The first published reference to any critical care nurse resource support was a critical care nurse consultant role to medical surgical wards in the United Kingdom.…”
Section: Critical Care Resource Nursementioning
confidence: 99%
“…Dawson and McEwen 12 reported on the positive impact of this nurse consultant on the care of the critically ill patient outside the traditional boundaries of the ICU. 11 Since then, there have been reports in Australia, Argentina, and Hong Kong of an ICU liaison nurse consultant role where the ICU RN follows patients discharged from the ICU. [13][14][15] Bloomer reported these nurse liaison models have shown an impact on post-ICU-discharge patients and recommended rethinking and evaluating the models of critical care.…”
Section: Critical Care Resource Nursementioning
confidence: 99%
See 2 more Smart Citations